Development of Augmented Reality Learning Media for Integrated Science and Social Studies (IPAS) Instruction to Improve Elementary School Students’ Conceptual Understanding - lindayani (Jurnal Humaniora Pendidikan (JHP), 2026)
This study aims to develop Augmented Reality (AR)-based learning media for Natural and Social Science (IPAS) subject in elementary schools to improve students' conceptual understanding. The research employed the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 32 fifth-grade students of SDN Gunong kleng. The instruments used included media expert validation sheets, content expert validation sheets, student response questionnaires, and concept understanding tests. Media expert validation obtained an average score of 88.5% (very feasible) and content expert validation 85.2% (very feasible). Field trials showed an improvement in students' conceptual understanding with an average pretest score of 61.3 increasing to 82.7 on the posttest, with an N-Gain of 0.55 (moderate category). Student responses to the AR media showed a very positive category with a score of 91.4%. Thus, Augmented Reality-based learning media is feasible and effective to use in IPAS learning in elementary schools